(3eYGfi GdbQGfs - (3CHh GdMSf SYjO Hf eSYOI GdeLGTYj HGdhdGA GdHdNj, GdCNaT GdGhSW,J (B215 (3g` s ((3CMeO Hf CHj eMeO GdeShi s)
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg (B( (3hGeQBJg MeGdI GdMWH (B) (3hbhdg hHYKfG efge GKfi YTQ fbjHkG s
(3BNQgG (B:s
(3hCeG bhdge Bejf agh eaJhM hCdag ebWhYI fbhd Bejf Ke Bejf hbO PcQ HYVge EfgG JNaa hjbGd ajgG Bejf s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B101s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1730s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs